If ChatGPT can do it, where is my creativity? generative AI boosts performance but diminishes experience in creative writing - Peidong Mei; Deborah N. Brewis; Fortune Nwaiwu; Deshan Sumanathilaka; Fernando Alva-Manchego; Joanna Demaree-Cotton (Computers in Human Behavior: Artificial Humans)
As generative AI (GenAI) becomes more sophisticated, it is increasingly being used as a tool to enhance creative expression and innovation. Along with its potential benefits, it is imperative that we examine pitfalls in how generative AI may affect the quality of creative thinking and possibly lead to a narrowing of diversity both in representation and thought. In this study, we employed an experimental design with 225 university students who completed a creative writing task with pre- and post-task surveys to assess ChatGPT's impact on their performance and experiences compared to a control group who did not use ChatGPT. Results show that using ChatGPT enhanced creativity of output and reduced the difficulty and effort required for the task, particularly for non-native English speakers. However, it also diminished the value and enjoyment of the task and raised moral concerns. We contribute to the nascent literature on GenAI by showing how ChatGPT assistance could potentially bolster human creativity by facilitating content delivery or providing useful counterpoint ideas. We also significantly advance scholarship on understanding experience of GenAI, demonstrating that bypassing the cognitive effort required for creativity by using ChatGPT could be harmful to the creative process and experience of creative tasks, especially when steps are not taken to address the use of AI in a transparent manner. Finally, our novel mixed-method study design offers a contribution to the methodological frameworks for the study of the effects and experience of GenAI. We discuss the study results in relation to implications for educational practices and social policy and argue that our results support recommending an integration of generative AI into higher education alongside practices that help to mitigate the negative impacts of AI use on student experience.